Approaches to Liberalizing Services - Stephenson, M. Sherry (The World Bank, 1999)
May 1999 - Liberalization of services at the subregional level has followed two broad approaches-the GATS model and the NAFTA model-neither of which automatically guarantees the full liberalization of trade in services. The question that participants in integration efforts at both the subregional and the broader regional level must ask is what kind of approach to liberalizing services offers both maximum transparency and the greatest degree of nondiscrimination for service suppliers. Only since completion of the Uruguay Round have developing countries in East Asia and the Western Hemisphere shown interest in liberalizing services. Ambitious efforts are now being made to incorporate services in liberalization objectives of both subregional and regional integration efforts, including in the Asia-Pacific region under APEC and in the Western Hemisphere under the Free Trade Area of the Americas (FTAA) process. At the subregional level, member countries of both ASEAN (in East Asia) and MERCOSUR (in Latin America) have chosen to follow the liberalization model set forth in the World Trade Organization's (WTO) General Agreement on Trade in Services (GATS), and to open their services markets gradually and piecemeal. In the Western Hemisphere, Mexico has successfully promoted the NAFTA model of a more comprehensive liberalization of services markets-and several Latin American countries have adopted the same approach. Regionally, APEC has chosen a concerted voluntary approach to liberalizing services markets. Within the Western Hemisphere, participants are defining which approach they will use in the negotiations on services launched as part of the FTAA in April 1998.